Involutions fixing F-n U F-3 - Barbaresco, Evelin M. [UNESP]; Pergher, Pedro L. Q. (Elsevier B.V., 2018)
Let Mm be a closed smooth manifold equipped with a smooth involution having fixed point set of the form F-n U F-3, where F-n and F-3 are submanifolds with dimensions n and 3, respectively, where 3 < n < m and with the normal bundles over F-n and F-3 being nonbounding. The authors of this paper, together with Patricia E. Desideri, previously showed that, when n is even, then m <= n + 4, which we call a small codimension phenomenon.-Further, they showed that this small bound is.best posiible. In this paper we study this problem for n odd, which is much more complicated, requiring more sophisticated techniques involving characteristic numbers. We show in this case that'm <= M(n - 3) + 6, where M(n) is the Stong Pergher number (see the definition of M(n) in Section 1). Further, we show that this bound is almost best possible, in the sense that there exists an example with m = M(n - 3) + 5, which means that for n odd the small codimension phenomenon does not occur and the bound in question is meaningful. The existence of these bounds is guaranteed by the famous Five Halves Theorem of J. Boardman, which establishes that, under the above hypotheses, m <= 5/2 n. (C) 2018 Royal Dutch Mathematical Society (KWG). Published by Elsevier B.V. All rights reserved.
Keywords: Involution; Fixed-data; Whitney number; Wu formula; Steenrod operation; Stong-Pergher number